Arousal dysregulation and executive dysfunction in attention deficit hyperactivity disorder (ADHD) - Isaac, Valeria; Lopez, Vladimir; Escobar, Maria Josefina (Frontiers in Psychiatry, 2024)
Attention deficit/hyperactivity disorder (ADHD) is a heterogeneous neurodevelopmental condition, that continues to have an elusive etiological background. A number of extant models and theories have historically intended to explain the many factors contributing to ADHD behaviors. One of the most accepted hypotheses has been the executive dysfunction theory associating reduction in executive control to abnormalities in structure and operational dysfunction of dopaminergic signaling networks. Nevertheless, executive functions are not always impaired in ADHD, and the literature describes other symptoms commonly reported suggesting individuals with ADHD would appear to suffer from a more general deficit. Another existing line of research, that has gained much attention recently, establishes that ADHD would have dysregulated states of brain arousal that would account for its commonly observed cognitive deficits and behavioral symptoms, described as the state regulation theory, which has now included measures of autonomic function.This article describes some important aspects that compose and challenge these two most influential theoretical constructs, executive dysfunction and state-regulation, based on their empirical evidence, implying the need to reevaluate the norms used to classify individuals and establish ADHD diagnosis. Large number of controversial results continue to exist within the study of ADHD biological and/or performance markers, possibly due to such heterogeneity and variability within the same diagnosis. The need to resolve these issues and establish newly revised diagnostic criteria for ADHD is critical, as therapeutic success depends on having accurately identified underlying neurophysiological factors in order to appropriately address them in treatment.